Interpretações paleoambientais com base nos icnofósseis da formação Serra do Tucano, Bacia do Tacutu - Ioris, Gabrielle Abreu Rodrigues (2015)
The Tacutu Basin is located in the extreme north of Brazil and has five Mesozoic lithostratigraphic units. Serra do Tucano Formation, Jurassic-cretaceous age, was chosen for the studies because it has a wide range of macrofossils, among them trace fossils. This study describes the trace fossils of invertebrates Serra do Tucano Formation, Tacutu Basin in Mesozoic, in order to weave paleoecological and paleoenvironmental interpretations based on the trace fossils. The specimens studied were collected in Morro do Tiro, Morro da Antena, Morro da Sereia and a roadblock margins of BR-401, the Paleontology Laboratory at Amazon (LAPA) of the Federal University of Roraima (UFRR), they are cataloged in the subcollection of Paleoicnology. They investigated a total of 28 samples of collection and 3 more in the field area, with 26 specimens of the Morro da Antena, 3 specimens of the Morro do Tiro and one specime for the roadblock and the Morro da Sereia. Five ichnogenus been recognized, namely, Coprinisphaera, Petroxestes, Teisseirei, Termitichnus and Thalassinoides, and two groups named here icno A and B described as yet undetermined material in the literature, constituting the first record for Brazil of the presented Ichnogens. Producers include molluscs, crustaceans, beetles, termites and caterpillars. The identified trace fossils reveal behaviors of nesting, construction of building structures, pupation to complete its metamorphosis and housing. The occurrence of these ichnogenus suggests an association of land and water or underwater environments.